AR420626, a selective agonist of GPR41/FFA3, suppresses growth of hepatocellular carcinoma cells by inducing apoptosis via HDAC inhibition. (March 2020) - Mikami, Daisuke; Kobayashi, Mamiko; Uwada, Junsuke; Yazawa, Takashi; Kamiyama, Kazuko; Nishimori, Kazuhisa; Nishikawa, Yudai; Nishikawa, Sho; Yokoi, Seiji; Taniguchi, Takanobu; Iwano, Masayuki
Background: Hepatocellular carcinoma (HCC) is a major cause of cancer death worldwide and establishment of new chemotherapies for HCC is urgently needed. GPR41 [free fatty acid receptor 3 (FFA3)] is a G protein-coupled receptor for short chain fatty acids, including acetate, propionate, and butyrate. In our previous study, we showed that propionate enhances the cytotoxic effect of cisplatin in HCC cells and that this mechanism is dependent on inhibition of histone deacetylases (HDACs) via GPR41/FFA3. However, the antitumor action of GPR41/FFA3 has not been elucidated. Methods: In this study, we examined AR420626 as a GPR41-selective agonist in HepG2 and HLE cells. Nude mice were used for HepG2 xenograft studies. The apoptotic effect of AR420626 was evaluated using flow cytometry analysis. Expression of apoptosis-related proteins and HDACs was evaluated by Western immunoblot. Gene silencing of HDAC 3/5/7 and GPR41 was performed using small interfering RNA. Expression of TNF-α mRNA was evaluated by TaqMan real-time polymerase chain reaction. Results: We found that AR420626, a selective GPR41/FFA3 agonist, suppressed growth of HepG2 xenografts and inhibited proliferation of HCC cells by inducing apoptosis. AR420626 induced proteasome activation through mTOR phosphorylation, which reduced HDAC proteins, and then increased expression of TNF-α. Conclusion: AR420626, a selective GPR41/FFA3 agonist, may be a candidate as a therapeutic agent for HCC.